Cursed - Calonita, Jen (Calonita, Jen. Fairy Tale Reform School., 2020)
Gilly and her friends at Fairy Tale Reform School try to stop Rumpelstiltskin from getting the ingredients he needs to cast a curse that will erase Enchantasia forever. Gilly hopes to activate the fairy skills she inherited from her fairy grandmother to stop Stiltskin, and in the process, save her sister Anna who is part of the evil Stiltskin Squad.